Acceptability of locally‐produced Ready‐to‐Use Supplementary Food (RUSF) for children under two years in Cambodia: A cluster randomised trial. Issue 3 (20th February 2019) - Borg, Bindi; Mihrshahi, Seema; Griffin, Mark; Sok, Daream; Chhoun, Chamnan; Laillou, Arnaud; Wieringa, Frank T.
Abstract: In Cambodia, existing food products for treating or preventing undernutrition have met with limited success. Therefore, in 2014, alternative ready‐to‐use foods were developed. This trial aimed to assess the acceptability of the novel ready‐to‐use supplementary food (RUSF) as a snack or mixed with borbor (white rice porridge), compared with corn–soy blend plus plus (CSB++) and borbor fortified with micronutrient powder (MNP). The nonblinded, randomised 4 × 4 crossover trial recruited 95 children aged 9–23 months from communities in peri‐urban Phnom Penh. Small quantities (100 g for porridges, 42 g for snack) of each food were offered for three consecutive days at testing sites (homes of health volunteers). Main outcomes were children's consumption, caregivers' assessment of children's preferences, and caregivers' ranking of the foods. Median percentage consumed of the test food servings ranged from 21 to 50% ( p  = 0.003). The odds of children consuming over 50% were greatest for borbor fortified with MNP versus RUSF snack (unadjusted OR = 6.79, CI = 2.80–16.47, p  < 0.001). However, the median energy children received when consuming the RUSF with borbor (57 kcals) or as a snack (48 kcals) was greater than with CSB++ (15 kcals) or borbor fortified with MNP (18 kcals; p  < 0.001). Therefore, although children ate less RUSF, it provided approximately three times more kilocalories. Caregivers reported that their children had the highest preference for borbor fortified with MNP. Caregivers themselves ranked the novel RUSF snack highest. Thus, the innovative RUSF was considered sufficiently acceptable to proceed to an effectiveness trial.